高等教育經費補助政策與績效分析：以臺灣公立大學與頂尖大學為例 Efficiency Analysis of Subsidiary and Grant Policy in Public Universities and Top Universities in Taiwan - 葉怡芬 Yi-Fen Yeh (National Taiwan Normal University, 2017)
在經濟不景氣時，高等教育常被詬病辦學經費（包含教育支出與研究支出）較中、小學為高，且易被質疑經費使用的有效性。本研究透過資料包絡分析（Data Envelopment Analysis）法，就研究傾向較高的 40 所大學進行研發績效評比，以及探討「邁向頂尖大學計畫」成員學校於兩期計畫中研發技術的成長。結果指出，長期國內大學排名為首的大學（如：臺灣大學、清華大學）在投入成本較他校為多的情況下，研發產能仍為高效率；科技大學的研發產能在 考量投入成本後，績效也為高效率；惟教學型大學可能因學科特性與投注較多於教育推廣，於考量成本與研發產能的績效則為落後。頂尖大學計畫的成員學校於計畫補助的二期內（2006-2014年，共三階段），研發的技術效率多有維持或進步，技術變革於階段三也已全面提升，惟規模效率的降低是多校的隱憂。績效分析結果雖無法代替校務分析，但其方法與結果可作為校內院所或校際間良性競爭的形成性評量與校務政策修正參考。 Higher education is often criticized for its relatively high cost to students, and universities generally incur high research costs. In this study, the research efficiency of 40 public universities was compared using data envelopment analysis. Additionally, member institutes of the project "Aim for the Top University" were evaluated for their research performance during project execution. The results indicated a high level of technical efficiency among top-tier universities (including National Taiwan University and National Tsing Hua University), even though they incurred relatively higher research costs. A high level of technical efficiency was also identified in many technology universities, particularly in terms of research output quality and comparatively low costs. Lower levels of technical efficiency were found for education-focused universities, likely because of their comparatively high expenditure and time on community education. The research capabilities of most member institutions improved with project funding during 2006-2014, even though scale inefficiency was a major concern. Efficiency analysis cannot substitute institutional research; nevertheless, the findings of the estimated efficiency and gaps can be valuable considerations for the evaluated universities.